Analysis of the truth in advertising on the efficacy provided by assisted reproduction clinics - Aznar, Juan; Tudela, Julio; Aznar, Justo (Acta Bioethica, 2017)
This paper analyses the efficacy data from assisted reproduction clinics, obtained from both scientific society reports and from studies published in specialised journals, in order to compare them with information published by Spanish assisted reproduction clinics on their websites. It aims to verify whether this information matches the reality of the findings in the media analysed or, in contrast, differs from the aforementioned scientific evidence. Our study shows marked discrepancies between the evidence of existing statistical data, and figures published by most of the clinics on their websites, which could constitute false advertising.